FRAUD: A BED-ROCK OF DISHONESTY-WORLD VIEW - I, Omah (European Scientific Journal, ESJ, 2013)
Purpose: The contention of this study is to highlight the magnitude effect of fraud perpetration (world over) on the parental sovereign nation/organization as the victim of circumstance, to determine the effects on stakeholders value and the general public, to recommend a lasting solution that can aid in curbing further attempts by the fraud managers, that will put them in a tight corner against any form of dishonest act. Methodology/Approach: Data collection was based on periodicals, Newspapers and CBN guidelines. A close contact with the affected institutions/parastatals were completely non and void due to inaccessibility to the stakeholders of the institutions. Structured questionnaire was disseminated to the highly interested public, numbering one hundred and twenty (120), who were keenly absorbed in the team of research topic. One-line discussions were applied to closely related friends and wellknown individuals on the subject matter at length. Literature review was empirically utilized in the study. Findings: Fraud, absolutely is the bed rock of dishonesty, which begets, unpatriotism. This category of people dismiss morality as unnecessary pre-requisite for virtuous life. To them the end justifies the means, thy are usually unscrupulous and opportunist in their endeavor to emeses wealth. Wealth by all practical wisdom is the subject matter. In the â€œBanana Governmentâ€, they do not fear evil nor respect the legal framework of the sovereign system in which they live and operate. They dominate the corridor of power. They are the â€œKiller searching for the killerâ€. They operate in an environment of unequal instability and dubious to the core. To them the economy can bread to death and the masses of the public can go to hell. Originality/Value: This paper virtually highlights the down-trend of an economy in the threshold of debacled society, battered by evils of dishonest and unpatriotic individuals in the public sector financial institutions as well as governmental sector of the economy. This paper under estimate the evils perpetrated by these â€œPower lordsâ€ in the corridor of power, in which the scorching effect of their act is being perceived by the poor masses seeking for a better governance of the day. Research Implication: Data procurement through the source evidence has been the main stumbling block in this research work, therefore, the researcher decided to compliment the data collection through the opinion of the closely related insiders and the public responses on the subject matter. Financial constraint, apart from limitations in data procurement has equally influenced the progress of the work adversely.